Pelatihan Penyusunan LKPD Eksperimen Sederhana untuk Guru Kimia Sampang Jawa Timur - Bertha Yonata; Utiya Azizah; Mitarlis Mitarlis (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Technological developments must be followed by all lines of education even with limited facilities and infrastructure. Educators need to prepare themselves with technological advances such as in internet-assisted learning so that learning can be interesting and contextual. The occurrence of events that cause face-to-face learning in conventional classes cannot be implemented must be handled wisely and appropriately. This requires appropriate skills, including laboratory activities. If laboratory activities, especially in chemistry subjects, are not carried out at all, they will not achieve the competence of higher order thinking skills (including critical and creative thinking skills) and laboratory activity skills. However, not all chemistry teachers in Sampang Regency, East Java have experience developing experimental worksheets, even though they have experience in developing worksheets that contain a collection of questions. For this reason, training is needed for teachers who will prepare simple experimental worksheets that support distance learning or blended learning. LKPD that helps higher order thinking skills is important to help teachers guide students not only to fulfill laboratory skills but also to prepare students with higher order thinking skills. This is also a demand for the curriculum in Indonesia (K13). The use of tools and materials that are easily found around students in simple chemistry experiments will help students achieve basic competencies. The training will be held online from July to August 2021. The training participants as many as 12 chemistry teachers participated in the training with the final result being the development of a simple experimental chemistry worksheet. All participants responded positively to this training activity and wanted the training activities to be carried out for other topics.